2009
DOI: 10.1038/labinvest.2009.50
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of TTF-1/NKX2-1 through DNA hypermethylation and histone H3 modulation in thyroid carcinomas

Abstract: Thyroid transcription factor-1 (TTF-1), also known as NKX2-1, is a homeodomain containing transcriptional factor identified in thyroid, lung and central nervous system. In the thyroid, TTF-1 is essential for thyroid organogenesis and governs thyroid functions by regulating various thyroid-specific genes. We previously demonstrated that most differentiated thyroid neoplasms, including follicular adenomas/carcinomas and papillary carcinomas, express TTF-1 at both protein and mRNA levels. However, certain subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…Promoter hypermethylation and silencing of the TSHR gene have been documented in thyroid carcinomas (Xing et al 2003, Hoque et al 2005, and similar findings have been reported for NIS and pendrin (Venkataraman et al 1999, Neumann et al 2004, Xing 2007. Furthermore, the expression of TTF1, a transcription factor that regulates the expression of all thyroid-specific genes (Bingle 1997), has been found to be silenced in poorly differentiated thyroid cancers as a result of promoter hypermethylation and histone H3 modifications (Kondo et al 2009). …”
Section: Epigenetic Control Of Differentiationmentioning
confidence: 69%
See 1 more Smart Citation
“…Promoter hypermethylation and silencing of the TSHR gene have been documented in thyroid carcinomas (Xing et al 2003, Hoque et al 2005, and similar findings have been reported for NIS and pendrin (Venkataraman et al 1999, Neumann et al 2004, Xing 2007. Furthermore, the expression of TTF1, a transcription factor that regulates the expression of all thyroid-specific genes (Bingle 1997), has been found to be silenced in poorly differentiated thyroid cancers as a result of promoter hypermethylation and histone H3 modifications (Kondo et al 2009). …”
Section: Epigenetic Control Of Differentiationmentioning
confidence: 69%
“…As for the latter view, several lines of evidence indicate that epigenetic changes are early events in the tumorigenesis process, prompting Feinberg et al (2006) to propose an epigenetic progenitor origin of human cancer. The investigation of epigenetic mechanisms in cancer has been greatly facilitated by the development of the chromatin immunoprecipitation (ChIP) procedure, which has recently been used to obtain interesting data on the epigenetic status of human thyroid cancer cells (Kondo et al 2009). …”
Section: Epigenetic Gene Regulationmentioning
confidence: 99%
“…It was recently reported that TTF1 expression deficiency in thyroid cancers is caused by epigenetic modification in association with cancer progression. 25 However, there have been no studies on TTF1 gene methylation in lung cancers.…”
mentioning
confidence: 99%
“…Trichostatin A® acted pro-apoptotic and increased NIS mRNA expression in TC cell lines (Puppin et al, 2005;Shen & Chung, 2005;Kondo et al, 2009). mRNA expression of PDS was reduced by trichostatin A treatment (Zarnegar et al, 2002).…”
Section: Pre-clinical Compoundsmentioning
confidence: 98%
“…In a study on mRNA expression of NIS, Tg, TPO and TSH-R and on iodide uptake in the PTC cell line B-CPAP, 5-Azacytidine compared to ATRA and trichostatin was very effective: it was the only compound, which increased iodide uptake (Tuncel et al, 2007). Also 5-Aza-2'-deoxycytidine increased differentiation and restored NIS expression in FTC, PTC and ATC cell lines (Kondo et al, 2009). 5-Aza-2'-deoxycytidine also induced mRNA expression of type I iodothyronine-5'-deiodinase, another thyroid-specific protein (Mentrup et al, 2002 ).…”
Section: Compounds In Clinical Trialsmentioning
confidence: 99%